Early Music in the 21st Century - Mitchell, Mimi (New York, NY Oxford University Press, 2024)
"It is time to reimagine the early music movement. Ever since its inception, the movement has been chronicled, analyzed, supported, and criticized by an array of journalists, philosophers, musicologists, and performers. Now that historically informed performance is firmly established in the Western classical music landscape, it is imperative to consider what we would like our future to be. What are our hopes for this new century? Although many "re"-prefix words are used when discussing how the movement should go forward-we need to rethink, reevaluate, revive, reinvigorate, and reboot-many of them have a slightly negative undertone. There are, of course, things that are problematic in the movement, and it is important to voice and confront these concerns. The term "early music" is itself debatable. Once a clear defining marker of the movement's repertoire, "early music" now feels too limited for a field that explores nineteenth- and twentieth-century music. More contemporary terminology, such as "historically informed," is equally problematic. As one modern player remarked, "What am I, historically uninformed?" With all its baggage and inadequacies, "early music" is still the term used to describe the movement's specialist journals, festivals, music departments, and concert series. Perhaps we will find something more appropriate in the twenty-first century? This volume introduces new ways to research and think about early music, addresses various performative issues, offers pedagogical possibilities and new technological tools, and-perhaps most importantly in this new century-suggests ways we can engage with the present as well as with the past. These essays present a number of possible positive directions for the future, while simultaneously addressing the things we'd like to change."
Keywords: Early music; Historically informed performance; Musical interpretation; Historiography